2005
DOI: 10.1128/aem.71.9.5004-5013.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solar UV Radiation on Morphology and Photosynthesis of Filamentous Cyanobacterium Arthrospira platensis

Abstract: To study the impact of solar UV radiation (UVR) (280 to 400 nm) on the filamentous cyanobacterium Arthrospira (Spirulina) platensis, we examined the morphological changes and photosynthetic performance using an indoor-grown strain (which had not been exposed to sunlight for decades) and an outdoor-grown strain (which had been grown under sunlight for decades) while they were cultured with three solar radiation treatments: PAB (photosynthetically active radiation [PAR] plus UVR; 280 to 700 nm), PA (PAR plus UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 48 publications
6
125
1
5
Order By: Relevance
“…Previously, solar UVR was found to reduce photosynthetic O 2 evolution of A. platensis D-0083 (Wu et al, 2005b) under similar conditions as in the present study. Here, we demonstrated that presence of UV-A and UV-B resulted in significant inhibition of the effective quantum yield and growth of this species, though high levels of PAR caused most of the inhibition.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Previously, solar UVR was found to reduce photosynthetic O 2 evolution of A. platensis D-0083 (Wu et al, 2005b) under similar conditions as in the present study. Here, we demonstrated that presence of UV-A and UV-B resulted in significant inhibition of the effective quantum yield and growth of this species, though high levels of PAR caused most of the inhibition.…”
Section: Discussionsupporting
confidence: 56%
“…UVR inhibits photosynthesis of cyanobacteria (Sinha et al, 1995;Kumar et al, 1996;Han et al, 2003;Wu et al, 2005b) and other photosynthetic organisms (Häder et al, 2001;Gao et al, 2007b). High levels of UV-B may reduce phycobilisomesrelated fluorescence and PSII activity in Arthrospira (Rajagopal et al, 2000(Rajagopal et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations